Past Performance Handbook, 2nd Edition - Beausoleil, Joseph (Berrett-Koehler Publishers, 2010)
The Best Guide to Past Performance Evaluation in Government Contracting Just Got Better! The Past Performance Handbook has long been the resource contracting professionals have turned to for guidance on evaluating contractor performance and making award decisions in competitive acquisitions based on the evaluation results. Now this essential resource has been completely updated and revised to bring readers the most up-to-date information they need to conduct past performance evaluations. Past Performance Handbook: Applying Commercial Practices to Federal Procurement, Second Edition, not only includes a detailed explanation of the process of past performance evaluation, but also presents new approaches to standardizing assessment areas and rating scales, streamlining the source selection process, and ensuring that awards are made to the most qualified offerors. This thoroughly revised second edition offers: " Additional focus on the collaboration between the government and contractors in providing past performance information " Enhanced definitions of numerical scoring, adjectival ratings, color coding schema, and risk assessments -- all consistent with the current guidelines issued by the Department of Defense and the Office of Federal Procurement Policy (OFPP) " Updated citations from the Federal Acquisition Regulation, OFPP, and the Government Accountability Office (GAO) " Abridged GAO decisions that provide details for citations included in the text. Contracting officers and contractors working with the government will find value in every chapter of this updated edition